A knowledge hierarchy model for adaptive multi-agent systems. (28th March 2008) - Xiao, Liang; Greer, Des
Adaptivity in software is important since business processes, business rules and business terms constantly evolve. A radical solution is described that makes use of the inherent adaptivity of software agents. The Adaptive Agent Model (AAM) represents business knowledge in a hierarchical structure consisting of a business concepts layer, a business rules layer, and a business processes layer. Collectively, these form a knowledge base sourced from the business requirements, that is available to running agents. Such externalised knowledge is easily maintained. Using a case study, the knowledge hierarchy is described and its contribution to the goal of software adaptivity assessed.